Pollen Serum Specific IgE Sensitization in Respiratory Allergic Patients in Jakarta, Indonesia - Iris Rengganis; Agus Joko Susanto (Acta Medica Indonesiana)
Background: pollens from trees or grasses in Indonesia have a perennial distribution due to the tropical climate. However, pollen allergy has not been well studied. This study aimed to evaluate the profile of pollen IgE sensitization in respiratory allergic patients in Jakarta. Methods: this was a cross-sectional study in patients with a history of respiratory allergy in Jakarta, Indonesia between September and December 2016. Adult asthmatic patients aged 19-60 years were invited to undergo serum specific IgE testing at the Allergy and Immunology Clinic, Cipto Mangunkusumo Hospital, Jakarta. Patients were included if they showed at least one positive skin prick test with environmental allergens. Quantitative determination of specific IgE in serum was carried out by multiple allergosorbent (MAST) assays (Polycheck Allergy®, Biocheck GmbH, Munster, Germany).  Serum specific IgE levels of more than 0.35 kU/L or Class 1 was considered positive. Results: a total of 106 cases were eligible for analysis; 81 (76.4%) were women. Patients’ mean age was 38.8+12.1 (range 19-59) years old. 59.4% of patients have both asthma and allergic rhinitis. There are 9 (8.5%) patients positive for IgE-pollen sensitization; 8 among them showed sensitization to at least 2 pollens. Sensitivity to goosefoot pollen is the highest (5.7%), followed by rye pollen (4.7%), plantain pollen (4.7%), wall pellitory pollen (4.7%), and Bermuda grass pollen (3.8%). Conclusion: although most pollens tested are not originated from native plants to Indonesia, a small number of patients showed specific IgE-sensitizations. Allergic persons planning to travel to the endemic areas of the relevant pollen should be advised. A panel of pollen allergens from local plants is highly desired.